Coronary artery spasm of different degrees as cause of angina at rest with ST segment depression and elevation. Issue 1 (July 1979) - De Servi, S; Specchia, G; Angoli, L
Abstract : Chest pain induced by ergometrine was associated with ST depression and subsequent elevation in anterior leads in a 42-year-old man suffering from angina at rest. Coronary arteriography during the attack showed that coronary arterial spasm of different degrees was responsible for chest pain and both types of electrocardiographic abnormality.